Digital agro‑advisory tools in the global south: a behavioural analysis of impacts, and future directions - Ofosu Ampong, Kingsley; Abera, Wuletawu; Mesfin, Tewodros; Abate, Tsion (Springer, 2025)
Digital agro-advisory tools have emerged as a promising solution to address pressing challenges in agriculture, particuarly for smallholder farmers in the Global South. This study provides a comprehensive characterisation of these tools, examining their behavioural typologies and adoption rates. Our desk and contextual review identified several digital agro-advisory tools in Global South. Our analysis revealed that low-adoption tools primarily focus on information dis- semination and post-harvest loss reduction. Moderate-adoption tools emphasize financial inclusion and early warning systems. High-adoption tools, on the other hand, prioritise climate-smart agriculture, farmer empowerment, and collaborative platforms. In all, our characterisation revealed five behavioural typologies necessary for the adoption of digital agro-advisory tools in the Global South. Critically, we found that trust is the fundamental foundation that determines adoption and sustained use of digital agricultural tools in the Global South. To scale up the adoption of these tools, it is crucial to address key constraints such as digital literacy, infrastructure, and policy environments. Additionally, our review shows that inclusive design and requirement elicitation are essential to ensure that these tools are accessible and relevant to the needs of smallholder farmers. By investing in digital infrastructure, promoting digital literacy, and fostering collaboration between stakeholders, we can harness the transformative potential of digital agro-advisory tools to create a more sustainable and equitable agricultural future.